The Europeanization of national polities? citizenship and support in a post-enlargement union - Sanders, David 1950- (Oxford Oxford University Press, 2012)
This volume studies the levels and evolution of EU citizens' attitudes toward the EU by answering 3 key questions: How widespread is the sense of European citizenship? What are its core drivers? And what consequences does citizenship have, if any, for EU support and for active political participation in EU politics?
Keywords: European Union -- Public opinion; Citizenship -- Europe; Europe -- Politics and government -- 1989-.